Summertime sleepers : animals that estivate - Stewart, Melissa (Charlesbridge, 2021)
Estivation is just like hibernation - only it happens in summer instead of winter. Why do some animals settle into cool, snug spots and sink into a summertime sleep? Because it's too hot for their bodies to function, or their food is in short supply. Some estivating animals sleep groups; others rest alone. Some go on a long journey before they slumber; others hunker down right at home. From the pixie frog to the spotted turtle to the desert hedgehog, discover how a variety of animals survive by taking a break during the hottest days of the year.